Kepustakawanan dalam Manajemen Kurikulum 2013 di SMA Muhammadiyah 1 Yogyakarta - Rahmi Yunita; Rilci Kurnia Illahi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
This study aims at the role of librarians in implementing the 2013 curriculum at SMA Muhammadiyah 1 Yogyakarta. This research is field research with a naturalistic qualitative approach. Research with data collection techniques with in-depth interviews, direct observation, and documentation at the Curriculum Wakaur and Library Coordinator of SMA Muhammadiyah 1 Yogyakarta as a key person. This study indicates that librarians play an important role in implementing the 2013 curriculum at SMA Muhammadiyah 1 Yogyakarta. The role of the librarian is seen indirectly in the form of literacy activities such as competitions and library-based learning.